How epistemic modifiers emerge - Mache, Jakob (Trends in linguistics. Studies and monographs ;, 2019)
This book delivers the first comprehensive study on German modal verbs which summarises and critically reflects the discussion of the last 500 years, checks these findings against large corpus data and is accessible to the English reader. It is shown that non-epistemic modal verbs modify events, whereas their epistemic counterparts modify the proposition, and how the latter developed from the former.